Plant Microtechniques and Protocols - Yeung, Edward Chee Tak; Stasolla, Claudio; Sumner, Michael John; Huang, Bing Quan (Springer International Publishing : Imprint: Springer, 2015)
This work gathers common plant microtechniques and updates their procedures using a simple and fully understandable approach.  The text serves as a handy resource for scientists familiar with the protocols and as a guide for the novice, especially students just beginning to learn about various structural methods for the first time.  This book analyzes a range of topics in order to generate cross-talks among scientists in different research disciplines. The first section of this volume covers the more commonly used embedding methods, with emphasis on the preparative methods for light and electron microscopy. A number of cell biology related protocols are compiled in the second section to showcase the usefulness of various techniques based on different processing and staining methods. The third section highlights some common and recent procedures in wood preparation. The last section includes botanical methods related to archaeological uses of plant materials. A special chapter on field and herbarium procedures is also included to serve as a guide to students interested in plant collection and taxonomic studies.